ADHD - New Directions in Diagnosis and Treatment 2015
DOI: 10.5772/61416
|View full text |Cite
|
Sign up to set email alerts
|

Family Difficulties in Children with ADHD, the Role of Integrated Psychopharmacology Psychotherapy Treatment

Abstract: Children with "DHD and their families face many challenges. The chapter discusses these difficulties with a case illustration. The write up of the case will demonstrate the difficulties faced by children with "DHD and their families highlighting how the difficulties in the parents impact the child s "DHD symptoms. The case illustration will demonstrate how normal the cases can be, and often are missed or dismissed, yet it causes distress to the children and the adults. The chapter hopes to raise awareness that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 156 publications
(272 reference statements)
0
2
0
Order By: Relevance
“…Importantly, in Mentor-UP mentees are supported by caring mentors who show affection and avoid punishment. This might be particularly relevant, considering that, in general, youths showing some degree of inattention and hyperactivity are used to experience relational contexts characterized by high levels of frustration and distress, which can result in punishments and reprimands from adults (parents, teachers, sport instructors) (Aili et al, 2015;Foley, 2011). The literature on ADHD showed that symptoms of hyperactivity and inattention are associated with that type of sensitivity to reinforcement contingencies (Kohls et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in Mentor-UP mentees are supported by caring mentors who show affection and avoid punishment. This might be particularly relevant, considering that, in general, youths showing some degree of inattention and hyperactivity are used to experience relational contexts characterized by high levels of frustration and distress, which can result in punishments and reprimands from adults (parents, teachers, sport instructors) (Aili et al, 2015;Foley, 2011). The literature on ADHD showed that symptoms of hyperactivity and inattention are associated with that type of sensitivity to reinforcement contingencies (Kohls et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Children with ADHD have higher activity levels, combined with the inability to control their temper as compared with age‐matched peers (American Psychiatric Association, 2013). Children with ADHD face obstacles in social relationships and in academics, which parents perceive as a burden (Aili et al., 2015; Lan et al., 2015). In Hong Kong, parents are the main caregivers of children with ADHD (Lan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%